The Legal Status of Platform Workers in Light of the Saudi Labor Law: An Analytical Study - Hadeel Ali Alamri (International Journal of Law Research and Studies, 2026)
This study addresses the legal status of workers on digital platforms in light of the Saudi Labor Law, amid the emergence of a novel form of work driven by the digital transformation and based on technological intermediation between service providers and beneficiaries, and the difficulty this raises in characterizing the relationship between the worker and the platform and the extent of its subjection to the provisions of the Labor Law. The study adopts the analytical approach in examining the relevant statutory texts; it clarifies the nature, characteristics, and types of digital platforms, then analyzes the statutory elements of the work relationship (natural personhood, work, wage, and subordination) and the extent of their applicability to platform workers, focusing on subordination as the decisive criterion and the novel form it has assumed in the digital environment, known as "electronic subordination." The study concludes that Article Two of the Labor Law—through its flexible wording "even if away from the employer's supervision"—encompasses this form, and that the characterization of the worker–platform relationship in location-based platforms is that of a subordinate employment relationship governed by the Law. It then sets out the effects of this characterization in terms of the rights and obligations of the three parties to the relationship: the worker, the platform as the employer, and the beneficiary. The study recommends addressing the legislative gap by amending the Labor Law and issuing dedicated regulations that clarify the legal status of these workers.
Keywords: Digital Platforms; Legal Status; Saudi Labor Law; Electronic Subordination; Employment Contract; Relationship Characterization